2019
DOI: 10.1038/s41394-019-0158-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of closed reduction of cervical spine injuries in a cohort of Nigerians

Abstract: Study design A prospective observational study. Objectives To evaluate the effectiveness of closed reduction of cervical spine injuries (CSIs) using cervical traction and identify probable complications. Setting Methods Consecutive CSIs managed by closed reduction using Gardener-Well's Tongs traction were prospectively analysed. The data included imaging and neurological examinations findings, Frankel grading, and extent of reduction. Reduction of 95% or more was deemed satisfactory. The primary outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In addition, the complications of reduction in a closed manner were over-distraction most commonly, tong pull-out, new-onset or worsening pain, and finally skull perforation. However, they concluded that satisfactory reduction can be achieved in patients with cervical spine injuries and significant malalignment [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the complications of reduction in a closed manner were over-distraction most commonly, tong pull-out, new-onset or worsening pain, and finally skull perforation. However, they concluded that satisfactory reduction can be achieved in patients with cervical spine injuries and significant malalignment [17].…”
Section: Discussionmentioning
confidence: 99%
“…There is no accepted upper limit to the weight that can be used to reduce these injuries; however, weights up to 140 lb (63.5 kg) have been reported as tolerated for reduction of facet dislocations 31,32 . On average, for unilateral facet dislocations, 10 lb (4.5 kg) per level above the jumped facets will be required in order to reduce the dislocation (i.e., the more caudal the dislocation, the more weight is necessary for reduction).…”
Section: The Role Of Preoperative Closed Reductionmentioning
confidence: 99%